Nível de flexibilidade da coluna lombar e a relação com atividade física, sedentarismo, dor e estado nutricional em escolares - Soares, Marcus Vinícius Flores (2013)
Introduction: The flexibility is defined as the maximum range of motion in one or more joints without the risk of injury. She may suffer influences of postural dysfunctions, and other sedentary. Objective: To investigate the level of flexibility of the lumbar spine and hamstring muscles in adolescents and its relationship with physical activity, sedentary, pain and nutritional status. Method: This was a crosssectional study in 2009 school year, with 524 elementary students enrolled in 5th through 8th grades in all five urban municipal elementary schools in Bauru (SP), aged between 10 and 15 years of age. We used structured protocol, the PAQ - C and measured the flexibility of the lumbar spine and hamstrings. There were descriptive and bivariate analysis. Results: We observed the distribution of students by sex boys (53.1%) and (46.9 %) girls, with the majority 13 (22.3 %) and 14 (27.9%) years of age; higher prevalence of sedentary and obese schoolchildren in both sexes, and appropriate level of flexibility not pointing in the vast majority of students. Conclusion: However, the results of this study allow us to conclude that the factors related to the excessive time that students remain seated in front of the computer and television, as well as participation in non-oriented physical activities, contribute to inadequate flexibility of the spine lower back and hamstring muscles